Morphological and phenotypic markers of connective tissue dysplasia patients with varicose veins lower limb - E. A. Zaharyan (Zaporožskij Medicinskij Žurnal)
The features of structure of the vein and integuments are found in the patients with undifferentiated СТD at histological and immunohistochemical study in comparison with the group with a minimum number of stigma: an hypotrophy of smooth-muscle fibers of the veins of the lower extremities; areas of a hypertrophy of the endothelial and subendothelial layers of the vein; deformation and sclerosis of the wall of vein; intensifying of an expression of collagen I type or reduction of III type; dystrophia of epidermis of the skin; deformation of collagen in derma on a background of a hypertrophy of areas of a stratum granulosum; disturbance of a vascular permeability; a perivascular lymphocytic infiltration in derma. It is confirmed, that detailed phenotypical features of severe connective-tissue dysplasia on frequency of occurrence and peculiarities coincide with morphological and immunohistochemical stigma of connective tissue dysplasia, describing severity of the disease, a resistance to therapy of trophic ulcers, frequency of relapses of disease of veins. It can have prognostic value and determine the intensity of therapy and as a whole therapeutic approach.